Polyurethane/D-LDH nanocomposites : effects of particle size on shape memory properties - Lew, Jun Heng. (2013)
The effect of nano-size filler, layered-double-hydroxide (LDH) on shape memory behavior of polyurethane (PU) nanocomposites was evaluated in this report. The shape memory PU matrix was prepared by polycaprolactone diol (PCL diol), 1,4-butane diol (BD) and 4,4’-methylenebis (phenyl isocyanate) (MDI) and the final PCL-based PU nanocomposites were synthesized by solution mixing with different size dopamine coated LDH fillers in an attempt to reinforce the shape memory PU nanocomposites and to obtain augmentation in shape recovery stress. The relationship between LDH filler size, structure and shape memory performance had been studied. In prior to enhance the interaction between filler and PU matrix, LDH was surface modified by a layer of dopamine, which is a compound that mimics mussel adhesive proteins. The modified LDH dispersed well in the polyurethane to form nanocomposites. From this study, the results showed that a 98% increase in the value of shape recovery stress with the addition of 2 wt% dopamine surface-modified LDH with dimension 38+-9 nm while exhibiting excellent shape fixity and recovery ratio.